Anger Management Berbasis Spiritual Care dalam Meningkatkan Regulasi Emosi Caregiver Klien Skizofrenia: A Systematic Review - Maulidiyah Junnatul Azizah Heru; Rizki Fitryasari; Hendy Muagiri Margono (FORIKES, 2021)
Background: Caregivers of schizophrenic clients are faced with various problems and caregiving burdens that can trigger stress and anger. Objective: To determine the effectiveness of spiritual-based anger management interventions in improving the emotional regulation of caregiver clients with schizophrenia. Methods: The sources of the articles used were obtained from searches through the Scopus database, Science Direct, and Proquest. The search for articles is limited from 2015 to 2020. After the articles are obtained, they are then reviewed until the stage of making a systematic review. The keywords used in the article search were “anger management”